2018
DOI: 10.1093/asj/sjx238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Facial Muscle Exercise Device on Facial Rejuvenation

Abstract: BackgroundThe efficacy of facial muscle exercises (FMEs) for facial rejuvenation is controversial. In the majority of previous studies, nonquantitative assessment tools were used to assess the benefits of FMEs.ObjectivesThis study examined the effectiveness of FMEs using a Pao (MTG, Nagoya, Japan) device to quantify facial rejuvenation.MethodsFifty females were asked to perform FMEs using a Pao device for 30 seconds twice a day for 8 weeks. Facial muscle thickness and cross-sectional area were measured sonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 38 publications
1
33
0
4
Order By: Relevance
“…As mentioned above, it is unclear whether training-induced increases in lip closure muscle strength are associated with improvement of age-related wrinkles and sagging [8], although one study reported those possibilities [9]. We believe that the evaluation of lip muscle function with the water bottle used in this study can also be used as a means of training for lip closure muscle strength.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As mentioned above, it is unclear whether training-induced increases in lip closure muscle strength are associated with improvement of age-related wrinkles and sagging [8], although one study reported those possibilities [9]. We believe that the evaluation of lip muscle function with the water bottle used in this study can also be used as a means of training for lip closure muscle strength.…”
Section: Discussionmentioning
confidence: 82%
“…Although it is unclear whether changes in facial muscle strength are involved in the loss of facial muscle and skin integrity with the generation of wrinkles and sagging [8], one study reported that wrinkles could be reduced by an exercise that involves holding an instrument in the mouth [9]. Furthermore, a recent case study reported lip and tongue exercise therapy as part of the orthodontic treatment for class three malocclusion [10].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies [15][16][17][18] were included in our analysis, totaling 188 adults ( Figure 1 and Table 2). Two of the four studies included compared the experimental group to a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Training conditions varied; neuromuscular electrical stimulation (NMES) was used in two studies, the other two studies used an oscillatory movement device and voluntary facial isometric exercise. Four studies [15][16][17][18] were included in our analysis, totaling 188 adults ( Figure 1 and Table 2). Two of the four studies included compared the experimental group to a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that atrophy of muscles as well as an increase in muscle cross-section after exercising can be followed with ultrasound, magnetic resonance imaging, and three-dimensional scanners. [31][32][33][34] A standardized study with regular planned follow-up visits, a standardized stimulation protocol, and use of patient questionnaires would be needed to verify the subjective improvement in symmetry and demonstrate the impact of ES in muscle response and psychological influence. 35 A larger sample size would be helpful to detect the between-group differences more accurately.…”
Section: Limitationsmentioning
confidence: 99%